DIPLOMASI MULTIJALUR PARIWISATA THAILAND DALAM MENINGKATKAN KUNJUNGAN WISATAWAN MANCANEGARA DI ERA NEW NORMAL TAHUN 2020-2022 - Olivia Zahrah (2023)
This study aims to analyze the diplomacy of the international tourism sector in Thailand during the crisis, especially in the new normal era, through multi-track tourism diplomacy to increase foreign tourist visits and efforts to return due to the crisis with various state and non-state actors. This research uses qualitative methods using primary and secondary data sources. In this analysis, the authors use the concept of international tourism and multi-track diplomacy. The final results of this study show that through the diplomatic efforts of the Tourism Authority of Thailand, Thai companies, through various platforms, have adapted to the new normal tourism situation. The various efforts made have succeeded in helping to increase tourist arrivals in Thailand. However, this figure has yet to succeed in keeping up with the number of foreign tourist arrivals before the COVID-19 pandemic, apart from that, as an adjustment to tourism in the new normal era, Thailand has also adopted various tourism security protocols adapted from global protocols.